Flexible Gas Detector - V. Kirakosyan; V. M. Aroutiounian
A version of gas detector using market sensors, as well as sensors developed in Yerevan State University is proposed (all sensors are resistive type). The main goal is to obtain a system model and a prototype based on it. The system is composed of both analog and digital parts.
Keywords: Physics; Instruments, apparatus, components common to several branches of physics; Materials science